Experiences of primary health care nurses advancing their careers in a remote Western Australian location. (19th July 2022) - Kagi, Elena; Rasiah, Rohan; Moran, Monica
Abstract: Objective: The objective of the study was to explore the experiences of primary health care (PHC) nurses advancing their careers in a remote location in Western Australia. Setting: The study was conducted in PHC organisations in one remote location in northern Western Australia. Participants: Six registered nurses working in four PHC organisations participated in the study. All were registered with the Nursing and Midwifery Board of Australia. Participants were all female, and five had child carer responsibilities. They had worked in the region for between 8 months and 10 years. Design: The design was based on a qualitative, interpretative phenomenological analysis methodology involving in‐depth, semi‐structured, face‐to‐face interviews. Results: Participants faced challenges advancing their careers given the limited employment opportunities and need to balance their professional ambitions with family needs. Participants had limited capacity to support each other's learning and felt poorly supported by employers to undertake professional development not directly related to their role. Participants were not well engaged with professional associations beyond undertaking online professional development activities provided with membership. Accessing professional development was difficult given a lack of time, limited access to local learning activities and a consequent need to travel, which was challenging. Despite the challenges they faced, most nurses remained passionate about their remote nursing roles and enjoyed the lifestyle. Conclusion: Remote PHC nurses face a range of challenges, some of which can be overcome by improved availability of local professional development and better support from employers and professional associations.